How Muslim defenders became "blood spilling" crusaders: Adam Gadahn’s critique of the "jihadist" subversion of Al Qaeda’s media warfare strategy - Kamolnick, Paul (Terrorism and political violence, 2017)
Adam Gadahn's Abbottabad letter offers a rare opportunity to examine how this Al Qaeda Senior Leadership (AQSL) media operative and spokesman conceptualizes and executes media warfare. In this article, I first introduce, depict, and employ the author's Terrorist Quadrangle Analysis (TQA) as a useful heuristic for conceptualizing and representing the four interrelated components of the AQSL terrorist enterprise: political objectives, media warfare, terrorist attacks, and strategic objectives. This TQA construct is then employed to conceptualize Gadahn's media warfare acumen. Gadahn is shown to be an adept communications warfare operative who conscientiously disaggregates and evaluates key target audiences, messengers, messaging, and media. Gadahn's vehement critique of select “jihadi” groups, in particular Tehrik-i-Taliban (TTP), al-Shabaab, and the Islamic State of Iraq (ISI), is then described. Key here is how and why Gadahn denounces their indiscriminate, murderous terrorist attacks on Muslim non-combatant civilians and other protected persons as effectively subverting his intended AQSL media warfare strategy and undermining AQSL strategic and religio-political objectives. A concluding section briefly summarizes these chief findings, offers select implications for scholarship and counter-AQSL messaging strategy, and identifies study limitations.